Dampak Perintah Atasan terhadap Kompetensi Auditor dalam menghadapi Kejujuran Profesional - Yulisfan; Muhammad Irsan Nasution (ARBITRASE: Journal of Economics and Accounting, 2024)
This study looks into how auditor competence responds to issues related to professional honesty when faced with superior orders. In order to evaluate auditor performance, a comprehensive strategy that takes into account qualitative, quantitative, and technical factors including integrity and professional honesty is required, as this study highlights. In order to preserve the quality of internal audits at the North Sumatra Regional Government, this study aims to ascertain the impact of superior’s instructions on auditor competence. This study employs a quantitative methodology with a population of auditors from North Sumatra's regencies and cities as well as the province government. A sample of 130 auditors was selected using the stratified random selection technique. Surveys were used to collect primary data, which were then analyzed using the Partial Least Square (PLS) method, which relies on the Structural Equation Modeling (SEM) equation model based on components or variations. The study's findings show that pressure or superiors' orders significantly and negatively affect an auditor's competency. The possibility that auditors will sacrifice their professional integrity in order to make the best use of their competence decreases with increasing pressure from superiors. In order to solve this issue, a number of tactical measures are suggested, such as enhancing external monitoring, guaranteeing internal audit independence, providing professional ethics training, and creating policies protecting whistleblowers. These actions should foster an atmosphere that upholds the independence and integrity of the auditors working for the North Sumatra Regional Government. Consequently, in order to uphold accountability and transparency in the use of public monies, auditors can do their tasks with the utmost integrity and professionalism. To reinforce professional integrity and increase audit effectiveness, this study offers crucial insights to financial managers, audit practitioners, and other stakeholders. A thorough grasp of the dynamics of the relationship between auditor competence and superior’s orders is anticipated to lead to a rise in awareness and cooperative efforts to support moral and high-quality auditing practices.